Analisis ketersediaan ruang terbuka hijau di Kota Tangerang Selatan - Fitri, Rini; Seanders, Olivia; Fauzi, Reza; Pangaribowo, R L (Jurnal Arsitektur Lansekap; Vol.8, No.2, Oktober 2022DO - 10.24843/JAL.2022.v08.i02.p13, 2022)
The need for land for urban development has an impact on changes in land use and the availability of green open spaces in urban areas. The increase in population from outside the area to urban areas will make the land in urban areas narrower and trigger a reduction in green open space. This study aims to determine the level of availability of green open space in the city of South Tangerang. The approach used in this research is a quantitative descriptive approach, namely field observation and field check, the research object of all green open spaces in the city of South Tangerang and data analysis using a geographic application system (GIS). The results showed that the change in green open space during the period 2010 to 2020 in the city of South Tangerang was 1,847 ha. The area of ??green open space available in South Tangerang City in 2020 based on the area is 4,224 ha. The area requirement for green open space required in South Tangerang City based on the area is 4,945 ha. The city of South Tangerang is still experiencing a lack of green open space of 721 ha.